Differential inductions of phenylalanine ammonia-lyase and chalcone synthase during wounding, salicylic acid treatment, and salinity stress in safflower, Carthamus tinctorius. Issue 3 (25th June 2014) - Dehghan, Sara; Sadeghi, Mahnaz; Pöppel, Anne; Fischer, Rainer; Lakes-Harlan, Reinhard; Kavousi, Hamid Reza; Vilcinskas, Andreas; Rahnamaeian, Mohammad
Abstract : Safflower ( Carthamus tinctorius L.) serves as a reference dicot for investigation of defence mechanisms in Asteraceae due to abundant secondary metabolites and high resistance/tolerance to environmental stresses. In plants, phenylpropanoid and flavonoid pathways are considered as two central defence signalling cascades in stress conditions. Here, we describe the isolation of two major genes in these pathways, Ct PAL (phenylalanine ammonia-lyase) and Ct CHS (chalcone synthase) in safflower along with monitoring their expression profiles in different stress circumstances. The aa (amino acid) sequence of isolated region of Ct PAL possesses the maximum identity up to 96% to its orthologue in Cynara scolymus, while that of Ct CHS retains the highest identity to its orthologue in Callistephus chinensis up to 96%. Experiments for gene expression profiling of Ct PAL and Ct CHS were performed after the treatment of seedlings with 0.1 and 1 mM SA (salicylic acid), wounding and salinity stress. The results of semi-quantitative RT–PCR revealed that both Ct PAL and Ct CHS genes are further responsive to higher concentration of SA with dissimilar patterns. Regarding wounding stress, Ct PAL gets slightly induced upon injury at 3 hat (hours after treatment) (hat), whereas Ct CHS gets greatly induced at 3 hat and levels off gradually afterward. Upon salinity stress, CtPAL displays a similar expression pattern by getting slightly induced at 3 hat, but Ct CHS exhibits a biphasic expression profile with two prominent peaks at 3 and 24 hat. These results substantiate the involvement of phenylpropanoid and particularly flavonoid pathways in safflower during wounding and especially salinity stress.